Biophysical Interactions in Fragmented Marine Canopies: Fundamental Processes, Consequences, and Upscaling - Folkard, Andrew M. (Frontiers in Marine Science, 2019)
Spatial fragmentation is a near-ubiquitous characteristic of marine canopies. Biophysical interactions with fragmented canopies are multi-faceted and have many significant implications at multiple scales. The aims of this paper are to review research on biophysical interactions in fragmented marine canopies, identify current gaps in knowledge and understanding, and propose ways forward. Although fragmented landscapes may be analyzed with relatively sophisticated approaches based on gradients and non-linear ecosystem interactions, it is argued that a simpler conceptualization in terms of patches and gaps is appropriate in this context. The review starts at the patch/gap scale and focuses initially on hydrodynamic interactions. It then considers the consequences of these interactions for particulate and dissolved material, and distributions of canopy-associated organisms. Finally, it addresses issues of upscaling to landscape scale and ways in which this research can be applied to marine landscape management, conservation and restoration. Work on a broad range of canopy types is considered, including micro-algal biofilms and turf algae; macro-algae, seagrasses and coral reefs; saltmarsh vegetation and mangroves. Although the focus is on marine canopies, insights from studies of fragmented canopies in other contexts are drawn on where relevant. These include freshwater environments and terrestrial forests, grasslands, crop canopies and urban areas. Specific areas requiring greater attention are highlighted. The review finds that more studies are needed of: wave interactions with patches and gaps; three-dimensional biophysical interactions with gaps; and biophysical interactions with fuzzy or indistinct patch/gap boundaries. More cross-comparisons of studies of hydrodynamic interactions with different types of canopies are also required. The primary obstacle to progress in this field is found to be the current gap between the most common scale for measurement and modelling – the patch/gap scale – and landscape scale, at which the insights delivered by research may be applied most usefully. Therefore, upscaling is identified as the most important current problem in this field. To address this, a combination of the recently-founded fields of eco-mechanics and hydrodynamics of aquatic ecosystems that balances physical, biological and other perspectives, rather than viewing one as being served by the others, would be the best way forward.